Age-related experiences of colorectal cancer diagnosis: a secondary analysis of the English National Cancer Patient Experience Survey. Issue 1 (3rd March 2023) - Owais, Syeda Somyyah; Arnolda, Gaston; Lamprell, Klay; Liauw, Winston; Delaney, Geoff P; Olver, Ian; Karnon, Jonathan; Braithwaite, Jeffrey
Abstract : Objective: The incidence of colorectal cancer (CRC) in people aged <50 years has been increasing dramatically in the past three decades and such patients are known to face difficulties in diagnosis. The objective of this study was to better understand the diagnostic experiences of patients with CRC and explore age-related differences in the proportion with positive experiences. Method: A secondary analysis of the English National Cancer Patient Experience Survey (CPES) 2017 was conducted on the responses of patients with CRC, restricted to those likely to have been diagnosed in the preceding 12 months via pathways other than routine screening. Ten diagnosis-related experience questions were identified, with responses to them categorised as positive, negative or uninformative. Age group-related difference in positive experiences were described and ORs estimated, both raw and adjusted for selected characteristics. Sensitivity analysis was performed by weighting survey responses to 2017 cancer registrations by strata defined by age group, sex and cancer site, to assess whether differential response patterns by these characteristics affected the estimated proportion of positive experiences. Results: The reported experiences of 3889 patients with CRC were analysed. There was a significant linear trend (p<0.0001) for 9 of 10 experience items, with older patients consistently displaying higher rates of positive experiences and patients aged 55–64 showing rates of positive experience intermediate between younger and older age groups. This was unaffected by differences in patient characteristics or CPES response rates. Conclusion: The highest rates of positive diagnosis-related experiences were reported by patients aged 65–74 or 75 years and older, and this is robust.